Comparação dos custos entre frota própria e terceirizada em uma transportadora do município de Mossoró/RN - Silva, Alysson Pereira da (Universidade Federal Rural do Semi-Árido, 2017)
Considering that transport is the logistic activity of significant importance regarding logistics costs. The objective of this article is to consider the use of outsourced freight as the most advantageous option for a Carrier, using the qualitative approach descriptive method for the objectives. The research is characterized as a case study on a carrier located in the municipality of Mossoró / RN. The analysis was carried out in 4 own transports with the same characteristics, making about 2 trips of 6 thousand km per month in the same stretch and route, totaling over 3 years an estimate of 432,000 kilometers traveled. The analysis of the costs with outsourced transport was made in the same stretch and equal route, with vehicle similar to the one used in the own transport with the same weight supported and the same amount of axles. For the analysis in question were compared trips of 6 thousand km traveled by own vehicle and 6 thousand km traveled by third party vehicle, under normal taxiing conditions. Therefore, it was inferred that the cost per kilometer of the Outsourced Fleet was the most advantageous when compared to the costs of Own Transport 1, 2 and 4. The Own Transport 3 was an exception due to its inactivity period, thus justifying its Lower value when compared to Outsourced Fleet.
Artigo
Keywords: Custos; Frota própria; Frota terceirizada; Costs; Own fleet; Outsourced fleet; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::CIENCIAS CONTABEIS